THE COOPERATIVE PRINCIPLE IN ZOOTOPIA (2016) MOVIE - Elyza Beauty Napitupulu; Ambalegin Ambalegin (Universitas Hasanuddin, 2022)
With the theory of Grice, this research carried out types of cooperative principles uttered by characters in Zootopia movie. Descriptive qualitative was the method of this research to explain the data. Observational method and non-participatory were used to collect the data by Sudaryanto. Following that to analyze the data, Pragmatic Identity Method was done to analyze the data in context and Matching technique was used to analyze the data. Four types of maxims in cooperative principle were found. The total of data was 54 data of maxims. It was found results of maxim quantity with 17 data, 14 data maxim of quality, 16 data for maxim of relevance, and maxim of manner with 7 data. Simply put, maxim of quantity was at the first rank as the most used data. Last, maxim of manner was the least data to use by the characters in Zootopia movie.